'The want of a proper Gardiner': late Georgian Scottish botanic gardeners as intermediaries of medical and scientific knowledge. Issue 4 (4th December 2019) - HICKMAN, CLARE
Abstract: Often overlooked by historians, specialist gardeners with an expert understanding of both native and exotic plant material were central to the teaching and research activities of university botanic gardens. In this article various interrelationships in the late Georgian period will be examined: between the gardener, the garden, the botanic collection, the medical school and ways of knowing. Foregrounding gardeners' narratives will shed light on the ways in which botanic material was gathered and utilized for teaching and research purposes, particularly for medical students, as well as highlighting the importance of the garden as a repository of botanic material for the classroom. In this way, the blurred lines between art and science, skill and scholarly activity, and shared pedagogic practices between botany and anatomy will be revealed.